Assessing the Possible Long-Term Effects of the Think Talk Write Model on Social Communication Competence in Primary School Students - Aramudin, Aramudin; Mukarromah, Omah; Faris, Didi; Susanti, R. Hariyani (Journal Of Education And Teaching Learning (JETL), 2025)
This study investigates the potential long-term effects of the Think Talk Write (TTW) model on the social communication competence of primary school students. TTW, an inquiry-based learning approach emphasizing collaborative thinking, discussion, and written reflection, has shown promise in improving immediate communication skills. However, its long-term impact on social competence, encompassing active listening, effective communication strategies, and empathy, remains under-researched. This study employs a class action research design to investigate the long-term impact of Think Talk Write (TTW) on social communication competence in fifth-grade students at MI Al-Hidayah Pekanbaru, Indonesia. Two intact classes (n = 17 each) will participate: the TTW group, exposed to TTW throughout the study, and the control group, receiving standard pedagogy. Specific evaluation tools will be utilized to assess the students’ social communication competence. The findings could inform pedagogical decisions and contribute to a nuanced understanding of how active learning environments foster well-rounded individuals with strong communication skills. The study found that the TTW model had a positive impact on students' social communication competence. Specifically, students in the TTW group showed significant improvements in their ability to: Actively listen to others, Express empathy, Resolve conflict, and Collaborate effectively.